2008
DOI: 10.1007/s00467-008-0867-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of reference values for plasma cystatin C and comparison with creatinine in premature infants

Abstract: Cystatin C (CysC) is a low-molecular-mass protein (13,343 dalton, 120 amino acids) belonging to the cystatin superfamily of reversible inhibitors of cysteine proteases. CysC appears to be eliminated from the circulation almost exclusively by glomerular filtration, which makes it a promising endogenous marker of renal function. CysC has been demonstrated to reflect glomerular filtration rate better than other low-molecular-weight proteins, including creatinine (Cr). We established reference values for serum Cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 13 publications
3
33
2
3
Order By: Relevance
“…Newman et al (26) showed that cystatin C was a better variable compared to creatinine in determining small changes in GFR in a study they performed in 469 patients. In a study performed in 108 preterm infants in Turkey, it was stated that cystatin C might be an option to evaluate renal functions, but it was not evaluated if it had superiority compared to creatinine and it was emphasized that this was related to the low number of subjects (27). In our study, no statistically significant difference was found between serum cystatin C levels measured on the third and 30th days in the patients who were fed enterally.…”
Section: Discussioncontrasting
confidence: 41%
“…Newman et al (26) showed that cystatin C was a better variable compared to creatinine in determining small changes in GFR in a study they performed in 469 patients. In a study performed in 108 preterm infants in Turkey, it was stated that cystatin C might be an option to evaluate renal functions, but it was not evaluated if it had superiority compared to creatinine and it was emphasized that this was related to the low number of subjects (27). In our study, no statistically significant difference was found between serum cystatin C levels measured on the third and 30th days in the patients who were fed enterally.…”
Section: Discussioncontrasting
confidence: 41%
“…However, its advantage over serum creatinine levels in the estimation of true GFR of infants has not yet been established, particularly in neonates [23,29] . In addition, the reference value for cystatin C in preterm infants has not yet been determined, although one previous study suggested upper limits of normal GFR of 2.10 and 1.95 mg/l at days 1 and 3 after birth [30] . Moreover, no study has yet examined whether increased serum cystatin C level can be a more useful marker in the diagnosis of intrinsic ARF than an increased serum creatinine level.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Cr, CysC is not affected by age, diet, or exercise, and since its concentration in the blood is dependent on the glomerular filtration rate, it has been reported to be a useful diagnostic biomarker in patients with AKI [18][19][20] except children, in whom the utility of CysC was limited and not considered to surpass that of Cr [21,22]. Recent studies, however, have shown that S-CysC is more useful biomarker for renal function than S-Cr even in children including neonates [23][24][25].…”
Section: Discussionmentioning
confidence: 99%